Effect of cytotoxic CD8+ T-cells secretory proteins on hypoxic pancreatic cancer cells. - Eiman Abdo; Mohammad A Ismail; Sabal Al Hadidi; Mairvat Al-Mrahleh; Tareq Saleh; Malik Zihlif; Nidaa A Ababneh (PLoS ONE, 2025)
Background Hypoxia in tumor cells is linked to increased drug resistance and more aggressive behavior. In pancreatic cancer, the tumor microenvironment is notably hypoxic and exhibits strong immunosuppressive properties. Given that immunotherapy is now approved for pancreatic cancer treatment, further understanding of how pancreatic tumor cell hypoxia influences T-cell cytotoxicityis essential. Objective This study examined how hypoxia affects the interaction between pancreatic tumor cells (PANC-1) and cytotoxic CD8+ T-cells. Methods Pancreatic tumor cells (PANC-1) were exposed to 20 cycles of chronic hypoxic conditions, each for 72 hours, followed by a re-oxygenation period for 24 hours. On cycles 10 and 20, PANC-1 conditioned media (CM) was harvested, and the hypoxic PANC-1 cells were co-cultured with either the activated cytotoxic CD8+ T-cells or with CD8+ T-cells CM. CD8+ T-cells CM was collected after five days of cell activation using anti-CD3/CD28 antibodies and interleukin-2 (IL-2). CD8+ T-cells were activated for 72 hours and then cultured with the hypoxic PANC-1 CM. Results Hypoxic PANC-1 cells showed significant resistance to the lytic effect of either CD8+ T-cells co-culture or CD8+ T-cells CM treatment compared to normoxic PANC-1 cells. A significant decrease in TNF-α and IFN-γ levels was also detected. Additionally, a significant increase in IL-6, p53 and TNF-α gene expression levels was observed in PANC-1 cells treated with CD8+ T-cells CM. Moreover, IL-6 gene expression level showed a significant difference between hypoxic and normoxic PANC-1 cells. CD8+ T-cell proliferation and cytokines production were significantly higher in cells co-cultured with PANC-1 CM. However, no significant differences were observed after treatment with either hypoxic or normoxic PANC-1 CM. Conclusion Hypoxia decreases PANC-1 cells' sensitivity to cytotoxic CD8+ T-cells. Reduced tumor cell susceptibility to CD8+ T-cells was associated with increased IL-6 expression and reduced TNF-α and IFN-γ levels. Thus, cytokine dysregulation might contribute to the hypoxia-mediated resistance of pancreatic tumor cells to CD8+ T-cells.